Regulation of Erotica and Pornography in the Public Sphere of Post-Independence Lithuania (1990–1996) - Bėčiūtė, Kotryna (Information & Media, 2024)
This article examines the state control of erotica in the public sphere and the activities of regulatory institutions in Lithuania between 1990 and 1996. Based on archival documents, the study reveals the methods used by the Press Control Commission and the Vilnius City Ethics Commission to regulate the distribution of erotica after the restoration of independence, and the criteria used by these institutions to assess sexualized content. A key issue in shaping a coherent legal discourse on the regulation of erotic and pornographic content is the ambiguity and blurring of the terms ‘erotica’ and ‘pornography.’ The study shows that these institutions sought to control erotic content primarily through three argumentative models: 1) the tradition and values model, 2) the “I know it when I see it” model, and 3) the threat of homosexuality model. The findings indicate a strong tendency within the Press Control Commission and the Vilnius City Ethics Commission not only to regulate (e.g., through age limits) but also to eliminate such content. The vague legal rulings and conceptual uncertainties of the 1990s gave these commissions considerable autonomy, allowing them to assume a proactive role that resembles that of an inquisitor or moral policeman.